Woman of the house : the rise of Nancy Pelosi - Bzdek, Vincent (New York : Palgrave Macmillan, 2008)
A portrait of the first woman Speaker of the House chronicles Nancy Pelosi's rise to political power, her role as a vocal opponent of the Iraq War, the legislative efforts she has spearheaded successfully, and her future in American politics
Includes bibliographical references and index.
Keywords: Pelosi, Nancy, -- 1940-; United States. -- Congress. -- House -- Speakers -- Biography; Women legislators -- United States -- Biography; Legislators -- United States -- Biography